Analysis of Mathematical Problem-Solving Skills of SMK Class XI Students in Statistics Material - Rika Agustina; Neneng Tita Rosita; Agus Jaenudin (MASI Mandiri Edukasi, 2026)
The purpose of this study is to characterize students' mathematical problem-solving skills in statistics using problem-solving indicators, such as comprehending the problem, coming up with a strategy, executing the plan, and looking back, as well as examining the different kinds of mistakes that students make. The study used a qualitative descriptive approach. Purposive sampling was used to choose twenty-eight eleventh-grade students from SMK Perkasa for the 2025–2026 school year as the subjects. The research tool was an essay test that assessed mathematical problem-solving skills. In order to examine the data, students' skills were divided into three categories: high, medium, and low. The proportion of mistakes for each indication was then determined. The findings indicate that pupils' aptitude for solving mathematical problems was typically classified as low. In all, 57.14% of pupils fell into the low group, 25.00% into the middle category, and 17.86% into the high category. Error rates were highest while implementing the solution plan (53%), followed by coming up with a strategy (41%), comprehending the problem (25%), and looking back (39%). These results show that pupils have trouble grasping procedures and doing computations accurately. Therefore, in order to enhance pupils' mathematical problem-solving skills, instructional efforts are needed.